DAMPAK KOREAN WAVE TERHADAP KRITERIA MEMILIH PASANGAN HIDUP PADA PENGGEMAR MUSLIM (Studi Kasus Penggemar K-pop di Lampung) - Irawan, Yufitri Syafia; Khuluq, Arif Husnul (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
South Korean culture is highly popular in many countries nowadays, including Indonesia. Slowly, the Korean Wave has shaped popular culture, influencing the thoughts and habits of its fans. This study aims to understand the impact of Muslim fans’ interest in K-Pop culture on their criteria for selecting a partner, specifically in Lampung. The researcher used a qualitative method with a case study approach, collecting data through interviews and observations. The research results show that enthusiasm and love for K-Pop affect the habits and thoughts of Muslim fans, particularly in partner selection criteria. The biggest impact of the Korean Wave on Muslim K-Pop fans in Lampung is related to partner characteristics, appearance, and physical attributes due to the portrayal of idealized idol traits. Simultaneously, Muslim fans still consider criteria set by Islam, such as religious values, good character, and assessing economic background, lineage, family, and educational background of potential partners.” Keywords: Korean Wave; Popular Culture; Partner Criteria; K-Pop.